Adherence of geriatric patients and their beliefs toward their medicines in the United Arab Emirates - Nihal A Ibrahim; Zehra Edis; Klaitham S Al-Owais (Wolters Kluwer Medknow Publications, 2020)
Introduction: Drug adherence is a major factor in determining health outcomes of geriatric patients and is a growing concern for health-care systems as the geriatric population shows a steep rise due to improved health-care services in the UAE. Aim: We aimed to evaluate the adherence and beliefs of geriatric patients in the UAE toward their medicines and to explore the factors affecting them. Methods: A cross-sectional study was performed including 163 geriatric patients. Surveys, direct observations, and interviews were used for primary data collection. Demographic data were computed using descriptive statistics method. The Statistical Package for the Social Sciences (SPSS) program, Version 19.0, SPSS Inc., Chicago, IL, USA, was used to analyze and code the raw data, whereas chi-squared test was used to analyze the responses. Secondary data were also collected. Results: The results indicated that patient factors and medication factors are the main risk factors for medication nonadherence among geriatric patients in the UAE. The study found that drug regimen (91.4%, N = 149), forgetfulness (87.1%, N = 142), time constraints (67.5%, N = 110), and cost (55.2%, N = 90) were the main key factors affecting medication adherence. Also, poor communication (12.9%), the lack of trust (16.6%), confidence (20.2%), and patient involvement (43.6%) were shown to influence adherence behaviors to medication. The main habits, attitudes, and beliefs that were found to affect patient's adherence were follow-ups (73%), inadequate knowledge of medicine (60.1%), the lack of perceived benefits (18.4%), and limited knowledge on health conditions (19.6%). The study showed 161 patients among the total 163 participants forget taking their medications and others cease from taking their medications. To conclude, nonadherence to medications is a substantial problem among the elderly in the UAE. Conclusion: The study findings confirm the need for further research to examine the perspectives of at-risk population with a focus on knowledge, beliefs, and attitudes on medication nonadherence.